Plan de negocios para la implementación del sistema Uht en la producción de leche entera de la empresa ABELLITO S.A - Morocho Marquez, Mauricio Alejandro (2022)
The High Temperature Treatment (UHT) system is used to reduce the number of microorganisms in whole milk, resulting in a high-quality ultra-pasteurized product. The objective of the work is to develop a business plan to determine the feasibility of implementing the UHT system in the company Abellito S.A., using the BMC (Business Model Canvas) methodology. Additionally, the PESTEL analysis and the CAME matrix were carried out to investigate the internal and external context, allowing for inputs that facilitate decision-making in the design of business strategies. Information was collected through an observation sheet applied in three supermarkets in Latacunga to show the preference of consumers for UHT milk. Based on the financial study, it was possible to demonstrate that the business plan is feasible because the profitability indicators are favorable for Abellito S.A.: IRR of 18.7%, NPV of $1,719.00 USD, Cost-benefit analysis (CBA) of $1.00, and a recovery period of one year.